2015
DOI: 10.1016/j.plantsci.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Phosphite cannot be used as a phosphorus source but is non-toxic for microalgae

Abstract: Phosphorous (P) plays a critical role for all living organisms as a structural component of RNA, DNA and phospholipids. Microalgae are autotrophs organisms that have been reported to only assimilate the fully oxidized phosphate (Pi) as P source. However, there are microorganisms capable of utilizing P reduced compounds (i.e. phosphite (Phi) and hypophosphite) as a sole P source, such as bacteria and cyanobacteria. In this study, we evaluated whether microalgae, such as Chlamydomonas reinhardtii, Botryococcus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 52 publications
1
36
0
1
Order By: Relevance
“…Because Phi is not metabolized by algae, algal bloom issues might be lessened in freshwater systems receiving P from farm runoff or tile drain leaching. The compound does not appear to be lethal to algae but inhibits growth through competition with OP much like the observations reported on terrestrial experiments (Loera‐Quezada et al, 2015). The rate of microbial oxidation from Phi to OP will likely dictate the efficacy with respect to this facet of the proposed system.…”
Section: Alternative Phosphorus Sourcessupporting
confidence: 72%
“…Because Phi is not metabolized by algae, algal bloom issues might be lessened in freshwater systems receiving P from farm runoff or tile drain leaching. The compound does not appear to be lethal to algae but inhibits growth through competition with OP much like the observations reported on terrestrial experiments (Loera‐Quezada et al, 2015). The rate of microbial oxidation from Phi to OP will likely dictate the efficacy with respect to this facet of the proposed system.…”
Section: Alternative Phosphorus Sourcessupporting
confidence: 72%
“…Previously, we reported that some microalgae (i.e. ; Botryococcus braunii and Ettlia oleoabundans ) were unable to metabolize Phi as a P source (Loera‐Quezada et al ., ). As part of this work, we determined that other microalgae including Haematococcus pluvialis and S. obliquus were also unable to metabolize Phi (Figure S3).…”
Section: Resultsmentioning
confidence: 97%
“…For this purpose, we tested the growth of cells harvested from media containing 1 mM Pi (P-replete cells) or from media devoid of a P source (P-starved cells) in medium supplemented with 0.1 mM Phi as P source in a Multicultivator photobioreactor (MC 1000, Qubit Systems; Qubit Biology Inc. Kingston, Ontario, Canada) ( Figure 1a). We tested Preplete and P-starved cells because we have previously observed that cells grown in 1 mM Pi are able to sustain significant growth in media lacking a P source (Loera-Quezada et al, 2015). We observed that after 6 days of cultivation in media containing Phi as a sole P source the putative ptxD transgenic lines were all capable of growing with a growth rate similar to that of the WT or the same transgenic lines in media containing Pi as a P source ( Figure 1; compare panel b versus c).…”
Section: Generation and Characterization Of Transgenic Chlamydomonas mentioning
confidence: 99%
See 1 more Smart Citation
“…La ausencia de efectos tóxicos de los fosfitos sobre el fitoplancton ya había sido demostrada con anterioridad. Concentraciones entre 7.9 y 158.17 mg/L de fosfito potásico monobásico no presentaron efectos tóxicos que causaran mortalidad de las células para la microalga Chlamydomonas reinhardtii (Loera-Quezada et al 2015). En el caso de la cianobacteria Microcystis aeruginosa, se ha observado que el fosfito parece ser inerte y no tóxico hasta concentraciones de 500 mg/L (Zhang et al 2011).…”
Section: Discussionunclassified